GLUCOSE SUPPLEMENTATION AND MEASURES OF OXIDATIVE STRESS IN PATIENTS WITH GLYCOGEN PHOSPHORYLASE DEFICIENCY (MCARDLE’S DISEASE). - Mocellin, Joseph Nicholas (My University, 2012)
Objective: We evaluated the potential effect of oral glucose supplementation on: (1) exercise performance and tolerance, (2) the concentrations of plasma uric acid and ammonia (NH3) and (3) blood plasma markers of oxidative stress in patients with McArdle’s disease (MCD) after non-ischemic forearm exercise testing (non-ischemic forearm exercise test). Methods: Blood samples and exercise performance measures were performed on from 16 patients with MCD and 17 control subjects (CON) matched for age, sex and physical activity status. Subjects performed 2 exercise bouts 30 minutes apart and received oral glucose or placebo supplementation between tests. Blood samples were analyzed for concentrations of 8-isoprostanes (8-ISO), malondialdehyde (MDA) and total anti-oxidant capacity (TEAC). Exercise performance was assessed using a handgrip dynamometer to measure force of contraction over time. Exercise tolerance was assessed based on subject’s self-reported perception of pain and perception of exertion during exercise. Results: MCD was associated with greater fatigue, perceived pain, perceived exertion, and higher uric acid during non-ischemic forearm exercise test (P < 0.05), and higher concentrations of plasma NH3 post exercise (P < 0.05). Glucose did not influence plasma uric acid or NH3 and had no effect on exercise measures in MCD patients. Baseline plasma markers of oxidative stress were not different between MCD patients and CON; however, MCD patients who ingested glucose between non-ischemic forearm exercise tests had lower plasma 8-ISO concentrations (P < 0.05). CON who ingested glucose between non-ischemic forearm exercise tests had lower plasma 8-ISO concentrations (P < 0.05) at +1 min post exercise compared to initial non-ischemic forearm exercise test. The TEAC of control subjects was lower following non-ischemic forearm exercise test (P < 0.05), with no change in MCD patients. Conclusion: Glucose may have a protective effect on oxidative stress following exercise that may be due to attenuated flux through xanthine oxidase.
Keywords: McArdles disease; oxidative stress; exercise; glucose supplementation; Biochemical Phenomena, Metabolism, and Nutrition; Medical Nutrition; Biochemical Phenomena, Metabolism, and Nutrition